Standardization Of Randang Meat Recipes In Nagari Tanjung Gadang, Tanjung Gadang District, Sijunjung District - Sahara Putri, Cut Mutia; Elida, Elida (Universitas Negeri Padang, 2022)
This type of research is a combined method of quantitative and qualitative descriptive methods. The research aims to find literature and sources regarding the recipe for Randang beef in Agam Regency which includes: ingredients, quantity of ingredients, how to make and quality of Randang meat, while quantitative methods are used to find the standard recipe for meat Randang in Sijunjung Regency and organoleptic testing of the quality of Randang meat aspects (shape, color, aroma, texture and taste). This research was conducted at Guguk Naneh Nagari Tanjung Gadang, Tanjung Gadang sub-district, Sijunjung Regency for 1 month in December 2020. The results of interviews and observations concluded that the quality of the meat cage was square, blackish brown. , fragrant coconut aroma and spices and savory taste. The standardization of the meat randang recipe includes the main ingredients, seasonings and spices used, the size of the converted ingredients, processing tools, processing methods and the quality of the meat randang. After organoleptic tests were carried out on 5 selected meat randang recipes from each jorong, the highest average value was obtained, namely the recipe belonging to Mrs. Erminawati from Jorong Guguak Naneh with an average value of 36.4.